Vote Buying Pada Pemilihan Duta Genre Perspektif Hukum Islam - Muflihin, Muflihin (Program Studi Hukum Ekonomi Syariah, 2024)
This research aims to find out the problems that occurred in the Wonosobo Regency GenRe Ambassador competition. The research method used in this study is field research, with qualitative data analysis. The results of this research show that the vote buying system in the Wonosobo Regency GenRe Ambassador competition uses money as a voting tool, where each person pays Rp. 1000 via QRIS to provide support. From the perspective of Islamic law, the use of money in voting is only a means of support and there is no explicit argument that forbids or allows it. Based on the muamalah principle